Association of macrophage inhibitory factor -173 gene polymorphism with biological behavior of prostate cancer - Razzaghi, Mohammad Reza; Mazloomfard, Mohammad Mohsen; Malekian, Sheida; Razzaghi, Zahra (Urology Journal, 2019)
Purpose: Chronic inflammation is an important factor in the etiology of prostate cancer. Macrophage migration inhibitory factor (MIF) plays an important regulatory role in inflammatory responses. The aim of this study was to investigate the potential association between MIF-173 G/C polymorphism, and both biological behavior and incidence of prostate cancer. Materials and Methods: Analysis of polymorphic variants for MIF was performed using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method in 128 subjects with prostate cancer and 135 controls. Results: The frequency of MIF-173 *C allele was significantly (OR = 2.18, 95% CI = 1.32-3.61) higher in patients with prostate cancer (19.5%) than in healthy individuals (10%). Prostate cancer patients with Gleason scores ? 7 had higher frequency of MIF-173 *C allele than Gleason scores < 7 (86.1% vs. 27.1%, P = 0.003, OR = 3.18, 95% CI = 1.46-6.95). The frequency of MIF-173 *C allele was significantly different in patients with T1, T2 and ?T3 clinical stages of prostate cancer (15.2% vs. 42.6% and 47.8%, P = 0.003). Conclusion: Our data suggest that MIF-173 polymorphisms may be associated with a higher incidence of prostate cancer compared to controls. We believe that MIF-173 GC+CC genotype can be used as a predictive factor for aggressive behavior of prostate cancer including pathological stage and Gleason scores as well as metastatic potential.